A Homeless Bill of Rights as a New Instrument to Protect the Rights of Homeless Persons. (3rd December 2020) - Ploszka, Adam
Abstract : Homelessness as a violation of human rights – Criminalisation of homelessness – Insufficient international and European protection of the rights of homeless persons – American charters of the rights of homeless persons as a source of inspiration – Model European Homeless Bill of Rights – FEANTSA – Human rights instrument – Positive and negative rights of the homeless person – Right to exit homelessness – Right to carry out practices necessary to survival within the law – Adoption and implementation of the Charter by Human Rights Cities in Spain, Slovenia and Poland – Soft law – Perspectives for the protection of the rights of homeless persons